METHODOLOGY FOR DEVELOPING SELF-DEFENSE SKILLS IN CADETS THROUGH COMBAT MARTIAL ARTS - Atashaykhov Abduvahid Abdushukurovich (Bright Mind Publishing, 2025)
This article covers the pedagogical and practical possibilities of combat solo sports in the formation and development of self-defense skills in cadets of higher military educational institutions. In the course of the research, a special methodology based on combat solo training was developed, and its effectiveness was based on experience-testing. The results obtained showed that this methodology is of high importance in increasing the physical, psychological and practical combat training of cadets.
Keywords: Cadet, combat solo, self-defense, physical training, military education, methodology